Continuous thermosalinograph oceanography along RV METEOR cruise track M208 - Schlundt, Michael; Brandt, Peter; Schulz, Marco; Dengler, Marcus (PANGAEA, 2025)
Underway temperature and salinity data was collected along the cruise track with two autonomous thermosalinograph (TSG) systems, each consisting of a SBE21 TSG together with a SBE38 Thermometer. Both systems worked independent from each other throughout the cruise. While temperature is taken at the water inlet in about 5 m depth, salinity is calculated within the interior TSG from conductivity and interior temperature. Temperature and salinity were validated against CTD data from 5 m depth. Finally, TSG1 was chosen for publication. For details to all processing steps see Data Processing Report.